Structure and Function of the d-Galactose Network in Enterobacteria - Zsolt Csiszovszki (American Society for Microbiology, 2011)
ABSTRACT Galactose is important for the survival and virulence of bacteria. In Escherichia coli, galactose is utilized by the Leloir pathway, which is controlled by a complex network. To shed light on the potential functions the galactose network could perform, we performed bioinformatical analysis of reference genome sequences belonging to the Enterobacteriaceae family. We found that several genomes have reduced numbers of components compared to the E. coli galactose system, suggesting that the network can be optimized for different environments. Typically, genes are removed by deletions; however, in Yersinia pestis, the galactose mutarotase (galM) gene is inactivated by a single-base-pair deletion. Lack of GalM activity indicates that the two anomers of d-galactose are used for different purposes, α-d-galactose as a carbon source and β-d-galactose for induction of UDP-galactose synthesis for biosynthetic glycosylation. We demonstrate that activity of the galM gene can be restored by different single-base-pair insertions. During the evolution of Y. pestis to become a vector-transmitted systemic pathogen, many genes were converted to pseudogenes. It is not clear whether pseudogenes are present to maintain meiotrophism or are in the process of elimination. Our results suggest that the galM pseudogene has not been deleted because its reactivation may be beneficial in certain environments. IMPORTANCE Evolution of bacteria to populate a new environment necessarily involves reengineering of their molecular network. Members of the Enterobacteriaceae family of bacteria have diverse lifestyles and can function in a wide range of environments. In this study we performed bioinformatical analysis of 34 reference genome sequences belonging to the Enterobacteriaceae family to gain insight into the natural diversity of the d-galactose utilization network. Our bioinformatical analysis shows that in several species, some genes of the network are completely missing or are inactivated by large deletions. The only exception is the galactose mutarotase (galM) gene of Yersinia pestis, which is converted to a pseudogene by a single-base-pair deletion. In this paper, we discuss the possible consequences of galM inactivation on network function. We suggest that galM was converted to a pseudogene rather than being deleted in evolution because its reactivation can be beneficial in certain environments.